New results on the global monotonie tracking of MIMO systems - Padula, Fabrizio; Ntogramatzidis, Lorenzo (2017)
© 2017 IEEE. In this paper, we consider the problem of achieving monotonic tracking control for any initial condition (also referred to as global monotonic tracking control). The main result of this paper is to show that in the strictly proper case, the solvability conditions can be greatly simplified with respect to the non-strictly proper case, and take a form that appears more insightful from a system-theoretic perspective.